Who was George Washington? - Edwards, Roberta; Illustrated by Kelley, True (New York Penguin Workshop, 2009)
"In 1789, George Washington became the first president of the United States. He has been called the father of our country for leading America through its early years. Washington also served in two major wars during his lifetime: the French and Indian War and the American Revolution"
Include Illustration and Bibliography
Keywords: Presidents -- Generals